PENERAPAN AKAD IJARAH PADA PEMBIAYAAN MULTI JASA DALAM PERSPEKTIF HUKUM ISLAM - Uswatun Hasanah; Rahmat Hidayat; Muhammad Zali (Smart Education, 2023)
Economic activities are increasingly complex along with the development of people's economic needs in modern times. Currently, there are many non-bank Islamic Financial Institutions that can help meet the needs of the consumptive community, such as the needs of members in the health and education sectors using ijarah contracts. The implementation is that the Islamic Financial Institution provides funds to members for education and hospital expenses, after which the members pay the Islamic Financial Institution in installments with a predetermined ujrah. After the author observes the implementation of ijarah contracts that are applied in multi-service financing such as education and health costs, these practices are not in accordance with Islamic law, because the meaning of services in ijarah contracts practiced by financial institutions is that service products owned by financial institutions are not services that are performed. by other parties.